Utility Regulators : The Independence Debate - Smith, Warrick (World Bank, Washington, DC, 2012)
Some governments are reluctant to surrender political control over regulatory decisions, and some who agree on the general desirability of independent agencies may question whether they are feasible in all country settings. The author argues that regulatory independence is worth the effort even in countries with little tradition of such government entities. The agencies should have arm's-length relationships with regulated firms, consumers, and politicians, and they should have the funding and expertise to underpin such independence. He explains the requirements for achieving independent agencies, including formal safeguards, and suggests possible paths of transition for setting up such agencies.